Enhancing Phenotyping and Molecular Analysis of Plant Root System Using Ultrasound Aeroponic Technology. Issue 4 (31st October 2018) - Pingault, Lise; Zogli, Prince; Brooks, Jennifer; Libault, Marc
Abstract: Several plant growth systems are available to enhance the observation of the root system (e.g., hydroponic and aeroponic plant growth systems, use of transparent soils, etc.). This article describes the use of the ultrasound aeroponic system (USAS) to treat and to enhance access to the root systems of various model plant and crop species (e.g., Arabidopsis thaliana, Medicago truncatula, soybean, etc.). This system is also compatible with short‐term (hr) and long‐term (days/weeks) biotic and abiotic treatments of plants. Upon treatment, the ease of access to the plant root system facilitates phenotyping (e.g., analysis of root architecture, establishment of root light spectrum using remote sensing technology), microscopic, molecular, and biochemical experiments. In addition, to facilitate functional genomic studies, we combined the use of the USAS with the hairy root transformation system to grow and observe transgenic roots on composite legume plants. © 2018 by John Wiley & Sons, Inc.